Discordance between the Indirect Object and the Atonic Pronoun le, a Growing Phenomenon - Caicedo Villa, Stella (Íkala, Revista de Lenguaje y Cultura, 2011)
In this descriptive, comparative and explanatory research, the phenomenon of discordance is examined between the indirect object and the atonic pronoun that doubles it in the sentence, in a corpus taken from the digital version of El Colombiano newspaper. With the help of Cratylus ® software frequencies of use of the discordance as well as the concordance were found, the grammatical structures of sentences, their grammatical number, the indirect object reference to thing and person was analyzed and finally results were compared. It is concluded that there is not only one explanation for the use of the discordance and probably it is a question of the phenomenon called fossilization. What indeed could be proved is the high frequency of disagreement detected in the cases when the atonic pronoun precedes the direct complement in the sentence.